2019
DOI: 10.1111/ics.12580
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Cró thermal water in a dermocosmetic formulation: cytotoxicity effects, characterization and stability studies and efficacy evaluation

Abstract: CONCLUSION: Cette etude a d emontr e pour la premi ere fois les avantages potentiels de l'eau thermale de Cr o dans une formulation de gel destin ee aux applications cosm etiques et dermatologiques.Thermal water-based gel dermocosmetic formulation F. Nunes et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Namely, thermal spring waters are associated with a wide range of therapeutic value such as anti-inflammatory, detergent, anti-pruriginous, keratoplastic, or antioxidant (Araujo et al, 2015). These kinds of waters also promote the control of skin hydration level, which is one of the most relevant bioindicators of the skin health (Nunes et al, 2019). An important source of these thermal and mineral waters is the Ourense province (Northwest of Spain), whose high thermal flow makes it the second city in Europe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, thermal spring waters are associated with a wide range of therapeutic value such as anti-inflammatory, detergent, anti-pruriginous, keratoplastic, or antioxidant (Araujo et al, 2015). These kinds of waters also promote the control of skin hydration level, which is one of the most relevant bioindicators of the skin health (Nunes et al, 2019). An important source of these thermal and mineral waters is the Ourense province (Northwest of Spain), whose high thermal flow makes it the second city in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…The thermo-mechanical properties of the biopolymer-based hydrogels are also highly dependent on the employed liquid phase, mainly when solvent with high mineral content are employed (Mao et al, 2020;Moreira et al, 2011;Priedniece et al, 2017). Consequently, the incorporation of mineral thermal waters on the formulation of starchy hydrogels could notably modify the texture and stability of the matrix (Lee & Lee, 2018;Nunes et al, 2019;Tai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This composition is responsible for promoting cellular renewal, skin hydration, recovery of cutaneous barrier function and keratolytic effects. In addition, it has been demonstrated that this water possesses antimicrobial, antioxidant and anti-inflammatory activities [23][24][25]. The potential of thermal water has been explored by different cosmetic companies, especially French ones, providing scientific evidence, through in vitro and in vivo studies, of the value of thermal water for the mentioned skin conditions, as recently reviewed [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have also used cell culture to determine the molecular mechanisms of TWs action at cutaneous level (Dal Pra, Chiarini et al 2007, Joly, Branka et al 2014, Karagülle, Karagülle et al 2018. Furthermore, thermal waters were successfully included as raw materials for dermocosmetic formulations to achieve the cutaneous welfare (Almeida, Madeira et al 2019, Nunes, Rodrigues et al 2019, Tan, Spada et al 2020.…”
Section: Introductionmentioning
confidence: 99%